Justice Under the Rainbow: Embracing Diversity in Posco Act, 2012 - Dr. Anju Choudhary; Ms. Rupali Mehta; Mehak Dalla (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The Protection of Children from Sexual Offences (POCSO) Act, 2012, is a significant statute in India aimed at protecting children from sexual abuse and exploitation. The Act's most notable characteristic is its gender-neutral approach, diverging from conventional legal standards that frequently categorize sexual offenses by gender. This study examines whether the POSCO act is gender neutral or it is more inclined towards one gender. This paper also examines whether third gender is covered under the act.